The Role of Allogeneic Stem Cell Transplantation in Relapsed/Refractory Hodgkin's Lymphoma Patients - Evgeny Klyuchnikov; Ulrike Bacher; Nicolaus Kröger; Ilya Kazantsev; Tatjana Zabelina; Francis Ayuk; Axel Rolf Zander (Advances in Hematology)
Despite the favorable prognosis of most patients with Hodgkin's Lymphoma (HL), 15–20% of patients remain refractory to chemoradiotherapy, and 20–40% experience relapses following autologous stem cell transplantation (SCT) being used as salvage approach in this situation. Long-term survival of only 20% was reported for patients who failed this option. As some authors suggested the presence of a graft versus HL effect, allogeneic SCT was introduced as a further option. Myeloablative strategies were reported to be able to achieve cure in some younger patients, but high nonrelapse mortality remains a problem. Reduced intensity conditioning, in turn, was found to be associated with high posttransplant relapse rates. As there is currently no standard in the management of HL patients who failed autologous SCT, we here review the literature on allogeneic stem cell transplantation in HL patients with a special focus on the outcomes and risk factors being reported in the largest studies.